Pengaruh Motivasi Kerja dan Kepuasan Kerja Terhadap Kinerja Karyawan Pada PB Suwela Amertha - Putra, Gede Esa Asta; Yulianthini, Ni Nyoman (Universitas Pendidikan Ganesha, 2020)
This study aims to examine the effect of: (1) work motivation on employee performance, (2) job satisfaction on employee performance, (3) work motivation on job satisfaction, (4) work motivation on employee performance through job satisfaction on PB Suwela Amerta. The research design used in this study is causal quantitative. The subjects of this study were all employees at PB Suwela Amerta. The object of this study were work motivation, job satisfaction and employee performance. The population used in this study amounted to 40 people. Data collected by questionnaire and analyzed by path analysis. The results showed that: (1) work motivation has a positive and significant effect on employee performance, (2) job satisfaction has a positive and significant effect on employee performance, (3) work motivation has a positive and significant effect on job satisfaction, (4) work motivation has a positive and significant effect on employee performance through satisfaction working at PB Suwela Amerta.